High-Temperature Tensile and Tribological Behavior of Hybrid (ZrB2+Al3Zr)/AA5052 In Situ Composite - Gautam G.; Kumar N.; Mohan A.; Gautam R.K.; Mohan S. (My University, 2025)
During service life, components such as piston, cylinder blocks, brakes, and discs/drums, have to work under high-temperature conditions. In order to have appropriate material for such applications high-temperature studies are important. Hybrid (ZrB2+Al3Zr)/AA5052 in situ composite has been investigated from ambient to 523 K (250 °C) at an interval of 50 deg. (ZrB2+Al3Zr)/AA5052 in situ composite has been fabricated by the direct melt reaction of AA5052 alloy with zirconium and boron salts. Microstructure studies show refinement in the grain size of base alloy on in situ formation of reinforcement particles. Al3Zr particles are observed in rectangular and polyhedron shapes. It is observed from the tensile studies that ultimate tensile strength, yield strength, and percentage elongation decrease with increase in test temperature. Similar kind of behavior is also observed for flow curve properties. The tensile results have also been correlated with fractography. Wear and friction results indicate that the wear rate increases with increase in normal load, whereas coefficient of friction shows decreasing trend. With increasing test temperature, wear rate exhibits a typical phenomenon. After an initial increase, wear rate follows a decreasing trend up to 423 K (150 °C), and finally a rapid increase is observed, whereas coefficient of friction increases continuously with increase in test temperature. The mechanisms responsible for the variation of wear and friction with different temperatures have been discussed in detail with the help of worn surfaces studies under scanning electron microscope (SEM) & 3D-profilometer and debris analysis by XRD. © 2016, The Minerals, Metals & Materials Society and ASM International.